Determinación de la huella de carbono en la Universidad Politécnica Salesiana, Sede Quito, Campus Sur. - Dávila Collaguazo, Fernando Jonathan (2014)
In this research it was determined the carbon footprint of the Salesian University, Quito headquarters, south campus; the value obtained for the year 2012 was 873.88 tons of carbon dioxide equivalent. The methodology used is the "Protocol greenhouse gas" that provides the calculation of three ranges, called Scopes. For UPS-South, the Scope 1 related to fuel use is 16.82 tonnes of CO2 eq, the same as Scope 2 has to do with power consumption of 209,07 t CO2 eq and Scope 3 that considers GHG emissions for the acquisition and use of inputs, by the decomposition of organic solid waste and liquid discharges, has a value of 647,99 t CO2 eq.